Use of copeptin and high-sensitive cardiac troponin T for diagnosis and prognosis in patients with diabetes mellitus and suspected acute myocardial infarction. (1st July 2015) - Zellweger, C.; Wildi, K.; Twerenbold, R.; Reichlin, T.; Naduvilekoot, A.; Neuhaus, J.D.; Balmelli, C.; Gabutti, M.; Al Afify, A.; Ballarino, P.; Jäger, C.; Druey, S.; et al.
Abstract: Background: Diabetes is a major risk factor for acute myocardial infarction (AMI). Assessment of diabetic patients is challenging due to an often atypical presentation of symptoms. We aimed to evaluate the two novel biomarkers copeptin and high-sensitive cardiac troponin (hs-TnT) for the improvement of early diagnosis and risk-stratification in patients with diabetes and suspected AMI. Methods: In this prospective international multicenter study we evaluated 379 patients with diabetes in a cohort of 1991 patients presenting with symptoms suggestive of AMI. The measurement of biomarkers was performed at presentation. Results: Among the 379 diabetic patients, 32.7% had AMI, and in the 1621 patients without diabetes, 18.8% had AMI. The additional use of copeptin improved the diagnostic accuracy provided by conventional troponin alone (AUC 0.86 vs. 0.79, p = 0.004). During a median follow-up of 814 days, 49 (13.1%) diabetic patients died. Cumulative 2-year survival rate for patients with copeptin levels below 9 pmol/l was 96.6% compared to 82.8% in patients above that level (p < 0.001). The same was observed for hs-TnT with a cutoff level of 14 ng/l (97.7% vs. 82.0%, p < 0.001) respective of cTnT with a cutoff level of 10 ng/l (93.5% vs. 75.6%, p < 0.001). In multivariate Cox analysis, copeptin, hs-TnT and cTnT were strong and independent predictors of 24-month-mortality. Using the dual marker strategy (copeptin and troponin) identified two groups of high-risk patients where 22.5% of the group with hs-cTnT and copeptin above the cutoff and 28.6% with cTnT and copeptin above the cutoff died. Conclusion: In diabetic patients, copeptin only slightly improves the early diagnosis of AMI provided by hs-cTnT. However, both markers (copeptin and troponin) predict long-term mortality accurately and independently of each other. Highlights: Copeptin and high-sensitivity cardiac troponin improved the early diagnosis of acute myocardial infarction in diabetic patients. High-sensitivity cardiac troponin and copeptin predict long-term mortality accurately and independently of each other. The combination of copeptin and high-sensitivity troponin further improved risk stratification by the identification of a group of diabetic patients at the highest risk for death.